Frequency of ischiofemoral space discrepancy when comparing magnetic resonance images of distinct institutions for the same patient. Issue 2 (4th March 2021) - Hatem, Munif; Martin, RobRoy L.; Nimmons, Scott J.; Martin, Hal David
Abstract: Inaccuracy of ischiofemoral space (IFS) measurement may result in radiographic misdiagnosis of ischiofemoral impingement, as well as insufficient or excessive osseous resection when surgery is indicated. This study compared the IFS measured in magnetic resonance imaging (MRI) performed in distinct health services for the same patient. Sixty-five patients (95 hips) who had hip MRI performed at an outside institution (noncontrolled MRI) followed by a hip MRI with lower extremity positioning reproducing the standing position (controlled MRI) were studied. For each hip, the IFS measured in the noncontrolled MRI was compared to the IFS measured in the controlled MRI. The categorization of a hip as presenting decreased IFS (≤17 mm) or normal IFS (>17 mm) changed in 19% of the hips when comparing the noncontrolled MRI to the controlled MRI. From the 32 hips (34%) with a difference ≥4 mm in the IFS, the predominant positioning change was hip flexion/extension in 47%, hip rotation in 44%, and hip abduction/adduction in 9%. In conclusion, a difference >4 mm in the IFS was observed in 1 out of every 3 hips when comparing noncontrolled MRI with controlled MRI reproducing the lower limb positioning in the standing position.